An evil day in Georgia : the killing of Coleman Osborn and the death penalty in the progressive-era South - Smith, Robert N. (Robert Neil) (The University of Tennessee Press, 2015)
"Follows a homicide case committed in Georgia in 1927 from the crime to the executions of those convicted of the crime almost a year later. Along the way, the narrative highlights a number of issues impacting the death penalty process, many of which are still relevant in the modern era of capital punishment in the United States ... Moreover, the case in question illustrates a range of themes prevalent in post-Progressive Georgia and brings them together to create a broader narrative. Thus, issues of race, class, and gender emerge from what was supposed to be a neutral process; ... demonstrates that capital punishment cannot be administered in an untainted fashion, but its finality demands that it must be"--From Athenaeum@UGA website.